Can we deconvolute electron density changes from the dominant influence of the atomic rearrangement on molecular excitation in time-resolved diffraction studies?. (4th January 2016) - Coppens, Philip; Zhang, Lei; Thomas, Ryan; Chen, Yang; Jarzembska, Katarzyna; Kaminski, Radoslaw; Trzop, Elzbieta; Fournier, Bertrand
Abstract: Recent studies have produced experimental triplet excited state structures with lifetimes of nanoseconds to microseconds. Photodifference maps, showing the total change on excitation, in principle include both the effect of the atomic shifts on excitation and that of the orbital transitions. The latter can be calculated theoretically thus achieving a formal deconvolution of the atomic and electronic shifts. In the three examples presented electronic shifts on excitation are orders of magnitude smaller than the effect of the atomic shifts and their electron shells and therefore not experimentally accessible at this time.